طريقة كروماتوغرافية جديدة لفصل الأوميبرازول عن نواتج تخربه وتحديده كمياً في مستحضراته الدوائية - توما مروان; سليمان منان; رجب أنس (Latakia University Journal -Basic Sciences Series, 2018)
تم تطوير طريقة كروماتوغرافية جديدة من أجل التحديد الكمي للأوميبرازول في مستحضراته الدوائية وإظهار كل من الأوميبرازول ونواتج تخربه منفصلة في كروماتوغرام واحد, وذلك باستخدام تقانة الكروماتوغرافية السائلة عالية الأداء HPLC. تم التحقق من صحة هذه الطريقة Validation بإجراء اختبارات الصحة والدقة والمجال والخطية والانتقائية/النوعية, ثم حسب كل من حد الكشف LODوالحد الكمي LOQ . New chromatographic method for Quantitative Determination of Omeprazole in its Pharmaceutical Products was produced. Omeprazole and its degradation components were well separated in same chromatogram by using by using high perfume liquid chromatography (HPLC). The new analytical method has been validated by these characteristic tests (accuracy, precision, range, linearity, specificity/selectivity, limit of detection (LOD) and limit of quantitative (LOQ) ).